A course in real analysis - Junghenn, Hugo D. (Hugo Dietrich) 1939- (CRC Press, Taylor & Francis Group, 2016)
A Course in real analysis provides a rigorous treatment of the foundations of differential and integral calculus at the advanced undergraduate level.